Public Trust in the Existence of Patronage Politic in the Distribution of Power in the Merah Putih Cabinet - Sari, Mulia; Naovallia, Sheila; Jalari, Rivi Ahmad; Anggraeni, Leni; Bestari, Yoga; Darmawan, Cecep (Pancasila and Civics Education Journal, 2025)
ABSTRACTIn the history of Indonesian politics, for the first time a cabinet of state ministries was formed with an extraordinarily large number of members, known as the Merah Putih cabinet. The existence of patronage politics is thought to be the main cause of the increase in the number of cabinet members. Therefore, researchers conducted research to determine public trust in the existence of patronage politics in the distribution of power in the Merah Putih cabinet using quantitative methods with a descriptive type. The results of research data processing using simple linear regression data analysis reveal that there is a positive influence that public trust has on the existence of patronage politics in the distribution of power in the merah putih cabinet, even though only 16.1%. This means that even though the level of trust is not very high, the public still believes in the existence of patronage politics in the distribution of power in the merah cabinet. One form of the existence of patronage politics is the public's belief that strategic positions in the Merah Putih cabinet are given to those who have political closeness to the leader. Keywords: Public Trust; Patronage Politic; Distribution of Power; Merah Putih Cabinet ABSTRAKDalam sejarah perpolitikan Indonesia, untuk pertama kalinya terbentuk kabinet kementerian negara dengan jumlah anggota yang luar biasa banyak yang disebut sebagai kabinet Merah Putih. Eksistensi politik patronase diduga menjadi penyebab utama menggemuknya jumlah anggota kabinet ini. Oleh karena itu, peneliti melakukan penelitian untuk mengetahui kepercayaan publik terhadap eksistensi politik patronase dalam pendistribusian kekuasaan kabinet merah putih melalui metode kuantitatif dengan tipe deskriptif. Hasil pengolahan data penelitian menggunakan analisis data regresi linear sederhana mengungkapkan adanya pengaruh positif yang diberikan kepercayaan publik terhadap eksistensi politik patronase dalam pendistribusian kekuasaan kabinet merah putih yaitu hanya sebesar 16,1%. Artinya walaupun tidak terlalu tinggi tingkat kepercayaannya, namun masyarakat tetap percaya terhadap eksistensi politik patronase dalam pendistribusian kekuasaan dalam kabinet merah putih. Salah satu bentuk eksistensi politik patronase tersebut adalah kepercayaan masyarakat bahwa jabatan-jabatan strategis dalam kabinet merah putih diberikan kepada mereka yang memiliki kedekatan politik dengan pemimpin.Kata Kunci: Kepercayaan Publik; Politik Patronase; Pembagian Kekuasaan; Kabinet Merah Putih